2021
DOI: 10.1136/bmjopen-2020-045012
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal characteristics and causes of stillbirth in a tertiary care hospital of Nepal: secondary analysis of registry-based surveillance data

Abstract: ObjectivesStillbirth is one of the vital indicators of quality care. This study aimed to determine maternal-fetal characteristics and causes of stillbirth in Nepal.DesignSecondary analysis of single-centred registry-based surveillance data.SettingThe study was conducted at the Department of Obstetrics and Gynecology, Chitwan Medical College Teaching Hospital, a tertiary care hospital located in Bharatpur, Nepal.ParticipantsAll deliveries of intrauterine fetal death, at or beyond 22 weeks’ period of gestation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
(31 reference statements)
1
11
0
1
Order By: Relevance
“…It is detected that most stillbirths occur in the age group 20-35 years. 15 In our study, mothers with primiparity constituted 42% of all stillbirths. This result is comparable to the few other studies.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…It is detected that most stillbirths occur in the age group 20-35 years. 15 In our study, mothers with primiparity constituted 42% of all stillbirths. This result is comparable to the few other studies.…”
Section: Discussionmentioning
confidence: 54%
“…12 The incidence of stillbirth in our study is comparable to the incidence of 19.6, 23.5 and 22 per 1000 births observed in some other studies. [13][14][15] Compared to available studies on stillbirth, the incidence of stillbirth found in this study is possibly the highest compared to other South Asian countries. 16 It is found that stillbirth is more common among mothers aged 20-25 years (43.65%) in this study.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The 12 Other studies done in Nepal from 2017-2019 and Ethiopia in 2018 showed similar results, where most of the cases have occurred at the age range of 21-30 years old (67.1%) and 20-34 years old (77.7%), respectively. 13,14 Stillbirth at 28 weeks gestation or after was more frequently seen in this study with a median of 30 weeks. Similar results were also reported in the United States of America from March 2020-September 2021, 55.8% with a median of 29 weeks.…”
Section: Discussionmentioning
confidence: 54%
“…6,12 Different results were also reported by a study in Nepal from 2017-2019, where one-third of stillbirth patients had unknown causes or possible causes of stillbirth. 13 Congenital abnormalities affect 31 (14.2%) stillbirth patients in this study. This finding is higher from the previous systematic review involving several countries worldwide, with an overall percentage of 11%, but lower than what was reported from a study in Qatar with the percentage of 21.6%.…”
Section: Discussionmentioning
confidence: 70%